Kajian Sistematis Efek Farmakologis dan Terapi Bunga Kamperfuli/ Ranggis (Lonicera japonica Thunb.) - Willie Japaries; Yelini Fan Hardi; Wijono Sukaputra Agussalim; Aryaprana Nando; Hari Kang Iskandar; Suryawan Suryawan (Institut Nalanda, 2023)
Background: Kamperfuli or Honeysuckle (Lonicera sp) is a decorative, food and medicinal plant quite widely used by the people. Various researches have been done on its and its bioactive substances’ usefulness for the therapy of various contagious and non-contagious diseases. Methods: This article is a systematic review of scientific research results on Lonicera sp and its bioactive substances published in the database of Researchgate, PubMed, and CNKI, especially within the last 10 years. Results: Chinese Pharmacope listed Honeysuckle in two separate entities as Jinyinhua (Lonicerae Japonicae Flos) and Shanyinhua (Lonicerae Flos) consisting of 5 species from genus Lonicera (L. japonica, L. confusa, L. macrantha, L. hypoglauca, and L. fulvotomentosa) with similar property and indications for heat elimination and detoxification. Various researches have proven its effects as antioxidant, anti-inflammatory, antimicrobial, anti-endotoxic, antidiabetic, neuroprotective, immunomodulation, etc. The medicinal parts include its flowers, leaves, and stems. Conclusions: The empirical effects of Honeysuckle have been proven scientifically. With its wide spectral pharmacologic effects, Honeysuckle can be used rationally as food, beverage, or natural remedy for health maintenance and help to treat various infectious due to microbes as well as non-infectious metabolic diseases.